Natural Medicinal Plants - El-Shemy, Hany A. (IntechOpen, 2022)
This book, Natural Medicinal Plants is a comprehensive overview of drugs derived from medicinal plants and their use in treating human illnesses such as cancer. Chapters include scientific evidence on flora rich in active ingredients.